Глаголы группы учить, учиться, изучать в аспекте системного подхода на уроках РКИ - Ковач, Екатерина; Поварницына, Марина (SlavVaria, 2022)
Studying of the Verbs Учить, Учится, Изучать in Terms of the System Approach. The verbs учить, учится, изучать are a complex system of meanings and lexical and grammatical relations that makes difficulties in acquiring of these verbs. The article offers some ways of working with this verb group based on system rela-tions, namely making lexical cards, clusters and sinkweins. These kinds of works give opportunity to use language system relations of the verbs and also to apply the system approach in teaching at different levels of studying this verb group in the course of Russian as a foreign language.